Efeito antioxidante e imunomodulador de um multissuplemento à base de guaraná, selênio e L-carnitina em modelos in vitro, in vivo e em pacientes com esclerose múltipla - Teixeira, Cibele Ferreira (2022)
Multiple sclerosis (MS) is an autoimmune, demyelinating, and neurodegenerative disease, which has neuroinflammation and oxidative stress as key parts of its pathogenesis. Among the clinical forms of the disease, is relapsing-remitting MS (RRMS), which affects approximately 85% of patients and is characterized by periods of neurological dysfunction (relapses) interspersed with periods of remission. Although different drugs are used to attenuate the progression of the disease, most patients have considerable disability and symptoms. In this sense, dietary supplements have been increasingly explored as possible adjuvants in improving the clinical picture of MS, but the existing data so far do not provide consistent evidence about the effectiveness of any supplement for this purpose. Thus, considering that a combination of compounds can provide more potent effects than an isolated compound and seeking substances with anti-inflammatory and antioxidant properties, a food multi supplement was developed, composed of a mixture of guarana (Paullinia cupana), selenium and Lcarnitine (GSC). Thus, the aim of this study was to evaluate the antioxidant and immunomodulatory effect of GSC in in vitro, in vivo models and in patients with MS. The work is divided into two articles: in article 1, the safety of GSC was evaluated, using concentrations equivalent to doses 1 to 50 times greater than the maximum recommended daily doses for each component: 0.04; 0.08; 0.12; 0.24; 0.50; 1.0; 2.1 mg/mL. The indicators analyzed were: (a) genotoxic and/or genoprotective capacity; (b) evaluation of oxidative, cytotoxicity and apoptotic markers in human leukocyte culture, treated for 24 hours with the 5 highest concentrations of GSC; (c) evaluation of the inflammatory activation of the microglia lineage (BV-2) treated for 72 hours with the 5 highest concentrations of GSC; (d) evaluation of the viability of red earthworms (Eisenia fetida) exposed to the highest concentration of GSC for 1, 3, 7 and 14 days, and evaluation of apoptotic events, oxidative markers and inflammatory activation of coelomocytes extracted after 3 days of earthworm exposure to the GSC. As a result, all GSC concentrations reversed the oxidation caused in DNA, suggesting genoprotective capacity. All concentrations maintained the levels of leukocyte oxidative markers equal to or lower than the control. GSC did not trigger extensive mortality in leukocytes, decreased apoptotic events, did not change the BAX/Bcl-2 ratio and caused downregulation in the expression of caspases 3 and 8, in relation to the control. In microglia, the highest concentrations induced cell proliferation, while the lowest decreased, in relation to the control. GSC did not induce earthworm mortality and no effect on apoptosis and most oxidative markers were observed in coelomocytes. GSC induced mitosis of coelomocytes and increased the relative frequency of amoebocytes, compared to control. There was a higher frequency of brown bodies and more extensive formation of extracellular networks in the coelom of earthworms treated with GSC than in the control. The results suggest that GSC may be safe for human consumption. In article 2, a pilot study similar to a clinical trial, double-blind, randomized, placebocontrolled, was carried out to investigate the effect of daily supplementation of GSC (G: 150 mg, S: 25 µg, C: 200 mg), for 12 weeks, in the modulation of liver and kidney function markers, oxidative stress markers and inflammatory markers in the blood of patients with RRMS. In total, 28 patients were included in the study and the GSC was able to decrease the plasma levels of oxidized DNA and proinflammatory cytokines, in addition to increasing the levels of the anti-inflammatory cytokine IL-10, without showing significant modulation in the other markers analyzed. The results support further research into the action of GSC on clinical symptoms, not only in MS patients, but also in other neurological and inflammatory conditions.